2002
DOI: 10.1016/s0926-6410(02)00139-8
|View full text |Cite
|
Sign up to set email alerts
|

MEG alpha activity decrease reflects destabilization of multistable percepts

Abstract: Multistable stimuli offer the possibility to investigate visual awareness, since they evoke spontaneous alternations between different perceptual interpretations of the same stimulus and, therefore, allow to dissociate perceptual from stimulus-driven mechanisms. In the present study, we used an ambiguous motion paradigm and compared endogenous reversals of perceived motion direction which occur spontaneously during constant ambiguous stimulation with exogenous reversals that were induced externally by changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
100
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(115 citation statements)
references
References 70 publications
12
100
3
Order By: Relevance
“…The finding that good perceptual performance is related to low alpha power has also been shown by Hanslmayr et al (2005). A variety of studies have shown that decreasing alpha power precedes the transitions between alternative perceptual representations of a multistable visual stimulus (Isoglu-Alkaç et al, 2000;Müller, Federspiel, Fallgatter, & Strik, 1999;Müller et al, 2005), findings confirmed in using magnetoencephalographic (MEG) measurements by Strüber and Herrmann (2002). Evidence for the potential of alpha activity for binding separate neural processes has been provided by von Sarnthein (2000, also von Stein, Chiang, &König, 2000) who have reported long-range fronto-parietal interactions in the theta and alpha frequency band during working memory retention and mental imagery.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…The finding that good perceptual performance is related to low alpha power has also been shown by Hanslmayr et al (2005). A variety of studies have shown that decreasing alpha power precedes the transitions between alternative perceptual representations of a multistable visual stimulus (Isoglu-Alkaç et al, 2000;Müller, Federspiel, Fallgatter, & Strik, 1999;Müller et al, 2005), findings confirmed in using magnetoencephalographic (MEG) measurements by Strüber and Herrmann (2002). Evidence for the potential of alpha activity for binding separate neural processes has been provided by von Sarnthein (2000, also von Stein, Chiang, &König, 2000) who have reported long-range fronto-parietal interactions in the theta and alpha frequency band during working memory retention and mental imagery.…”
Section: Introductionmentioning
confidence: 73%
“…A multidimensional scaling of co-occurrent hallucinatory experiences in Becker and Elliott (2006) ple; see Becker & Elliott for a full description of the pattern of inter-relationships between colors), implying the impossibility of these colors to be experienced at the same time. In this respect, the experience of hallucinatory color may be similar to the perception of multistable figures (Müller et al, 2005;Strüber & Herrmann, 2002), where one interpretation of the figure is deactivated and replaced by another interpretation. The decrease of alpha power preceding the report of hallucinatory color may reflect such a transition.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Using magnetoencephalographic (MEG) measurements, a continuous decrease of endogenous alpha activity was shown to precede the reversal between two stimulus interpretations [156]. In addition to changes in alpha activity, a role for gamma band activation during the perception of multistable figures has been claimed [157].…”
Section: Rationalementioning
confidence: 99%